Gender Agreement Attraction in Greek Comprehension - Paspali, Anastasia; Marinis, Theodoros (Frontiers in Psychology, 2020)
This work explores gender agreement attraction in comprehension. Attraction occurs when an agreement error (*the key to the cabinets are rusty) goes unnoticed leading to the illusion of grammaticality due to mismatch between the value of the head and the value of a local intervening phase (attractor). According to retrieval accounts, these errors occur during cue retrieval from memory and predict illusions of grammaticality. Alternatively, representational accounts predict that the errors occur due to the faulty representation of certain features, thus, illusions of ungrammaticality are also expected. In four experiments we explore a) whether gender agreement attraction occurs in Greek and the strategy/-ies employed, b) the role of agreement target, b) the timing of gender agreement attraction, c) the role of phonological matching between the nominal inflectional morphemes of the attractor and the agreement target, and d) participants’ sensitivity to agreement when there is no conflict from the attractor. In all four experiments, the grammaticality of the sentence and the attractor value (match/mismatch with the head) and also the phonological matching between the attractor and the agreement target in ungrammatical sentences were manipulated. The agreement target was an adjectival predicate or an object-clitic and the gender value of the head was feminine or neuter. Attraction was found in all measures during the time-course of adjectival predicates (Experiment 1) and object-clitics (Experiment 2), and in timed (Experiment 3) and untimed (Experiment 4) judgements. Even more, both gender values showed attraction and the results mainly suggest that participants experience illusions of grammaticality, confirming retrieval accounts. Phonological matching did not modulate attraction in any of the experiments, suggesting that the similarity in the morphophonological realization between the agreement target and the attractor does not increase attraction. Furthermore, participants were sensitive to gender agreement violations in the absence of gender mismatch between the head and the attractor, suggesting that they respect agreement rules and have both neuter and feminine available in their feature content repertoire, although with some tendency in favor of neuter in feminine agreement contexts. The impact of these findings is discussed within the concept of attraction and sensitivity to agreement violations.